PbS Quantum Dots-Decorated BiVO4 Photoanodes for Highly Efficient Photoelectrochemical Hydrogen Production - Joo-Won Seo; Seung-Beom Ha; In-Cheul Song; Jae-Yup Kim (Nanomaterials, 2023)
While metal oxides such as TiO2, Fe2O3, WO3, and BiVO4 have been previously studied for their potential as photoanodes in photoelectrochemical (PEC) hydrogen production, their relatively wide band-gap limits their photocurrent, making them unsuitable for the efficient utilization of incident visible light. To overcome this limitation, we propose a new approach for highly efficient PEC hydrogen production based on a novel photoanode composed of BiVO4/PbS quantum dots (QDs). Crystallized monoclinic BiVO4 films were prepared via a typical electrodeposition process, followed by the deposition of PbS QDs using a successive ionic layer adsorption and reaction (SILAR) method to form a p-n heterojunction. This is the first time that narrow band-gap QDs were applied to sensitize a BiVO4 photoelectrode. The PbS QDs were uniformly coated on the surface of nanoporous BiVO4, and their optical band-gap was reduced by increasing the number of SILAR cycles. However, this did not affect the crystal structure and optical properties of the BiVO4. By decorating the surface of BiVO4 with PbS QDs, the photocurrent was increased from 2.92 to 4.88 mA/cm2 (at 1.23 VRHE) for PEC hydrogen production, resulting from the enhanced light-harvesting capability arising from the narrow band-gap of the PbS QDs. Moreover, the introduction of a ZnS overlayer on the BiVO4/PbS QDs further improved the photocurrent to 5.19 mA/cm2, attributed to the reduction in interfacial charge recombination.